The The Effect of Giving The Antioxidant Vitamin C in Tris-Egg Yolk Extender During The Preservation Period on The Quality of The Epididymal Spermatozoa of Mice (Mus musculus L.) - Dewi, Efie Fadjrijah Eka; Mahriani, Mahriani (Universitas Jember, 2023)
Spermatozoa preservation is a method used to store spermatozoa in a diluent solution such as NaCl or tris-egg yolk. However, the longer storage of spermatozoa in the diluent solution can generally form ROS (Reactive Oxygen Species). The addition of antioxidants such as vitamin C to the diluent is expected to be able to bind ROS so that they are not toxic to spermatozoa and sperm quality can be maintained during the preservation period. The purpose of this study was to determine the effect of giving the antioxidant vitamin C in tris-egg yolk diluent during the preservation period on the quality of mice epididymal spermatozoa. Vitamin C used in this study was 0.5 mg, 1 mg, and 2 mg in 100 ml of tris-egg yolk diluent. Observation of spermatozoa quality was carried out within 0 to 48 hours with a span of 12 hours. The results showed that the addition of Vitamin C concentrations of 0.5 mg, 1 mg, and 2 mg in 100 ml of tris-egg yolk diluent was able to maintain the percentage of motility and vitality, but the longer the storage the quality of spermatozoa decreased. The concentration of vitamin C 0.5 mg, 1 mg, and 2 mg in 100 ml of tris-egg yolk diluent is a good concentration to maintain the quality of spermatozoa during 12 hours of storage, the rest will decrease. Further research is needed to increase the storage time of spermatozoa by using vitamin C and tris-egg yolk.